The Exposure and Hazards of Zinc Oxide Nanoparticles: In Vitro and In Vivo Studies - Parisa Saberi-Hasanabadi; Obeid M Malekshah; Hamidreza Mohammadi (Mazandaran University of Medical Sciences, 2023)
Background: Extensive application of zinc oxide nanoparticles has increased the likelihood of its release into the environment and subsequent human exposure and toxicity. The toxicity is thought to be a combined effect of intracellular particles and the release of dissolved zinc ions.  Objectives: This review outlines the possible mechanisms of zinc oxide toxicity in biological organs through in vitro and in vivo experiments.  Methods: We reviewed articles published between 2001 and 2021. In this way, we did a manual search of Google Scholar and scientific databases, including PubMed, Web of Science, Scopus, and Embase, with keywords such as "zinc oxide nanoparticles", "toxicity mechanism", and "in vivo and in vitro studies". The other qualified papers contained the history of identifying zinc oxide nanoparticles, the toxicity of metallic nanoparticles, and physical, chemical, and biological side effects with topical and systematic approaches. Results: The main mechanism suggested for zinc-based nanoparticles-induced cell damage is via the induction of increased levels of reactive oxygen species, which are oxidative stress markers. This mechanism has also been found to be a key mechanism for the cytotoxicity of other metal nanomaterials. Zinc-based nanoparticles were found to induce oxidative DNA damage, inflammation, progressive degenerative cell changes, cell cycle arrest, cytogenetic alterations, and ROS-triggered mitochondria-mediated apoptosis in human organs. Conclusion: This review sheds light on the full understanding of in vitro and in vivo toxicity assessment of zinc oxide nanoparticles, highlighting the health concerns from the perspective of ZnO nanoparticles release to the ecosystem after their increasing application.